Peculiarities of the Ontogenesis of Bacilli During Development from a Vegetative Cell to a Spore - Voitsekhovsky, V.G.; Avdeeva, L.V.; Balko, O.B.; Balko, O.I.; Войцеховський, В.Г.; Авдєєва, Л.В.; Балко, О.Б.; Балко, О.І. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Understanding the development processes of bacteria, in particular spore-forming ones, has both fundamental and applied importance, since at various stages of this process, the cells of microorganisms perform certain functions that can be regulated by influencing certain factors depending on the tasks. Literature data and the results of our research on the influence of the composition of the nutrient medium, pH, temperature, and aeration on sporulation are analyzed in the article. It isshown that the direction of bacterial cells’ development in certain ways is determined by signals that come from the surrounding environment, affect their genome, and determine the ways of cell development – growth or sporulation. Sporogenesis can also be induced by metabolites formed during microorganism development. It is emphasized that the environmental factors that influence the sporulation of bacteria have been studied in sufficient detail. However, the mechanisms of their action remain debatable. Morphological, genetic, and biochemical changes of spore-forming bacteria under the conditions of macrocyclic and microcyclic ways of their development are also highlighted, which makes it possible to correctly understand the functioning of regulatory mechanisms in the ontogenesis of microbial cells. In particular, the data of our research on the dynamics of morphological changes in the ontogenesis of a specific individual bacterial cell are presented. In addition, factors, including specific terminal products of cell metabolism, such as antibiotics, and genetic mechanisms of sporogenesis regulation of various genera and species of bacteria are described in detail. The nature of the vast majority of "sporogenes" has not been clarified, and there are only a few hypotheses regarding the mechanism of their action. However, most of the biological regulators of sporogenesis were found in the culture liquid, which indicates the cellular nature of their action. Therefore, to obtain more convincing data on the regulation of sporogenesis, studies at the cellular level are needed.